THE BALTIC BOOK CONTACTS: TRANSLATIONS OF LATVIAN AND LITHUANIAN LITERATURE IN THE ESTONIAN BOOK PRODUCTION - MÖLDRE, AILE (Knygotyra, 2010)
In the light of differing views on the development of the common Baltic identity, based on analogous historical, political, economic and cultural features, the paper studies its manifestation through translations from the Latvian and Lithuanian languages into Estonian. The analysis is based on a catalogue of translations, which has been compiled with the help of bibliographies and bibliographic databases. A statistical analysis of the data is used to establish the most active periods of translation publishing, the most popular authors and genres. The first book translation from Latvian dates back to the 18th century, whereas the first book translated from Lithuanian was issued in 1954. Until 1918 when all the three nations gained independence, cultural exchange in this region embraced only the historical Baltic provinces. Lithuania emerged in the cultural space of Estonians more intensively since the 1930s. The most productive period in translating Latvian and Lithuanian literature was the Soviet period when the Baltic unity reached its peak. After regaining independence, the feeling of Baltic identity has diminished alongside with the decline in publishing of books translated from Latvian and Lithuanian.
Keywords: Latvia; Lithuania; Estonia; the Baltic states; Baltic identity; translations; publishing; book production